Irritable bowel syndrome and role of pinaverium bromide: pharmacological profile and clinical efficacy - Bagepally, Ravi S. (International Journal of Research in Medical Sciences, 2024)
Irritable bowel syndrome (IBS) is a common gut brain interaction disorder that is diagnosed via patient-reported symptoms and various diagnostic criteria. Multiple factors, such as visceral hypersensitivity, gut dysbiosis, dysmotility, gut-brain dysregulation, lifestyle, and dietary habits, are involved in the development of IBS and manifestation of its symptoms of abdominal pain, bloating, and abnormal bowel movements. Lifestyle modifications and dietary changes, behavioral therapy, and pharmacological treatments, namely antispasmodics and antianxiety drugs, are commonly prescribed for IBS management. Pinaverium bromide is a selective calcium channel blocker that acts locally in the gastrointestinal tract and relieves spasms making it an effective agent for the treatment of IBS. This review provides a background on the diagnostic criteria and pathogenic mechanisms of IBS from an Indian clinician standpoint and provides an in-depth overview on clinical studies of pinaverium emphasizing its role in IBS treatment.